2020
DOI: 10.20960/nh.03051
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic effect of olive leaf extract on streptozotocin-induced diabetes mellitus in experimental animals

Abstract: Efecto antidiabético del extracto de hoja de olivo sobre la diabetes mellitus inducida por estreptozotocina en animales de experimentación Antidiabetic effect of olive leaf extract on streptozotocin-induced diabetes mellitus in experimental animals 10.20960/nh.03051 OR 3051 Antidiabetic effect of olive leaf extract on streptozotocininduced diabetes mellitus in experimental animals Efecto antidiabético del extracto de hoja de olivo sobre la diabetes mellitus inducida por estreptozotocina en animales de experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…Olive trees originate in the eastern Mediterranean and the Kingdom of Saudi Arabia, with compounds like oleuropein, flavonoids, and phenolics (Sofowora, 1996). Animal studies on the influences of olive leaves extracts or their components have revealed several therapeutic effects such as hypoglycemic, anti-tumor and antimicrobial activity (Gürbüz and Öğüt, 2020;Morandi et al, 2021;Sánchez-Gutiérrez et al, 2021). The present study may be the first investigation aimed to evaluate the influence of olive (Olea oleaster) leaves extract on male rats exposed to Cd.…”
Section: Advances Inmentioning
confidence: 86%
“…Olive trees originate in the eastern Mediterranean and the Kingdom of Saudi Arabia, with compounds like oleuropein, flavonoids, and phenolics (Sofowora, 1996). Animal studies on the influences of olive leaves extracts or their components have revealed several therapeutic effects such as hypoglycemic, anti-tumor and antimicrobial activity (Gürbüz and Öğüt, 2020;Morandi et al, 2021;Sánchez-Gutiérrez et al, 2021). The present study may be the first investigation aimed to evaluate the influence of olive (Olea oleaster) leaves extract on male rats exposed to Cd.…”
Section: Advances Inmentioning
confidence: 86%
“…Olive Leaf Extract is regarded as one of the most effective complementary therapies for the prevention and control of type 2 diabetes. The literature contains well-established in vitro studies on the effects of oleuropein on type 2 diabetic patients [48][49][50][51][52][53][54][55][56]. However, in silico analysis of the same thing is still an open area.…”
Section: Introductionmentioning
confidence: 99%